Novel Machining Technique for Surface Patterning by Diamond Turning - Neo, Wee Keong; Huang, Rui; Kumar, A. Senthil; Rahman, Mustafizur (8th International Conference on MicroManufacturing (ICOMM 2013), 2013)
This paper presents a novel method of machining image surface by diamond turning with fast tool servo (FTS). In the proposed methodology, three-dimensional pixel data [X, Y, Z] are extracted directly from a digital image via MATLAB image processing tool, which are pre-processed and super-imposed onto a three-dimensional spiral tool trajectory. The proposed methodology has been experimentally validated by the successful machining of freeform features based on any digital image. The freeform features can be designed in a manner in which is otherwise generated from complex equations. It allows even a layman to customize a feature without working out any mathematical equations
Keywords: polar coordination position; image surface; FTS Diamond turning